2022
DOI: 10.1371/journal.pbio.3001886
|View full text |Cite
|
Sign up to set email alerts
|

Systematic assessment of the replicability and generalizability of preclinical findings: Impact of protocol harmonization across laboratory sites

Abstract: The influence of protocol standardization between laboratories on their replicability of preclinical results has not been addressed in a systematic way. While standardization is considered good research practice as a means to control for undesired external noise (i.e., highly variable results), some reports suggest that standardized protocols may lead to idiosyncratic results, thus undermining replicability. Through the EQIPD consortium, a multi-lab collaboration between academic and industry partners, we aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Alternatively, labs developed a general protocol but adapted it to fit their own respective budget with what resources they had. Of note, recent work has suggested that harmonization reduces between-lab variability, however, systematic heterogenization did not reduce variability further ( Arroyo-Araujo et al, 2022 ); this may suggest that, even in fully harmonized protocols, enough uncontrolled heterogeneity exists that further purposeful heterogenization has little effect. Another barrier identified was ethics approval for animal experiments at all the labs ( Llovera et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, labs developed a general protocol but adapted it to fit their own respective budget with what resources they had. Of note, recent work has suggested that harmonization reduces between-lab variability, however, systematic heterogenization did not reduce variability further ( Arroyo-Araujo et al, 2022 ); this may suggest that, even in fully harmonized protocols, enough uncontrolled heterogeneity exists that further purposeful heterogenization has little effect. Another barrier identified was ethics approval for animal experiments at all the labs ( Llovera et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The multinational EQIPD consortium ( E nhanced Q uality in P reclinical D ata, https://quality-preclinical-data.eu/) aimed to identify factors influencing the quality of data generated in preclinical research as a basis for recommendations enabling a smoother and successful transition from preclinical research to clinical application (9, 10). In a recent study, the consortium analyzed the impact of protocol harmonization on the replicability of data in the open field test, i.e., a behavioral paradigm with automated recording of the primary outcome parameters (11). The study demonstrated that harmonization of protocols can reduce between-site variability (11).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the consortium analyzed the impact of protocol harmonization on the replicability of data in the open field test, i.e., a behavioral paradigm with automated recording of the primary outcome parameters (11). The study demonstrated that harmonization of protocols can reduce between-site variability (11). Considering that the standardized application of scoring systems and their harmonization across sites can pose a particular challenge, we next addressed the question of whether a comparable impact can be observed for a frequently used paradigm, based on scoring of a variety of readout parameters by experimenters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation